An Investigation Study Investigating Prospective Innovative Pedagogical Strategies For The Teaching Of Music In Institutions Of Higher Learning - Wei, Zhang (Journal of Neonatal Surgery, 2025)
Worldwide, more and more individuals are starting to understand the value of music pedagogy and systematic instruction. Because they are founded on instruction that is well-informed and research-based, piano lessons have the ability to connect the non-professional piano teaching sector with the academic world. In addition, the study investigates how these evaluations of the adequateness of their piano training might impact how they use different piano abilities while instructing students. The researcher included twelve distinct functional piano talents in the questionnaire they created. Improvisation, sight reading, accompaniment, playing piano repertoire, composition, techniques, literature that consumes scores, harmonisation, transposition, modulation, and melodic progressions were all part of this set of abilities. This study uses quantitative data to look at the relationships between music education and things like morality, people, psychological well-being, brain development, and creative problem-solving abilities. These results provide credence to the theory that musical exposure greatly improves children's overall competence. This study lends further weight to the hypothesis since it quantitatively assessed the links between music education and various skills. The research fills a need in the literature by doing a quantitative analysis of music education. The researchers also provide important recommendations for how colleges and universities might improve their involvement, curriculum development, and assessment in this area. This was examined in light of the globally recognized best practices by comparing it to group piano instruction in Malaysian school settings.